2021
DOI: 10.1088/1755-1315/947/1/012044
|View full text |Cite
|
Sign up to set email alerts
|

Use of wheat flour and spent coffee grounds in the production of cookies with high fiber and antioxidant content: Effects of spent coffee grounds ratio on the product quality

Abstract: Spent coffee ground (SCG) is the main by-product of the instant coffee industry. In this study, wheat flour and dried SCG powder were used in the production of cookies with high fiber and antioxidant content. The objective of the study was to evaluate the effects of SCG ratio in the cookie formulation on nutritional quality, physical properties and sensory overall acceptability of the product. SCG is a rich source of dietary fiber. In 100 g dry weight of SCG, the total fiber and phenolic contents were 76.6 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Previous studies attributed the antioxidant capacities of coffee and tea to their phenolic contents. ,, Our findings indicate that the residual phenolic compounds in spent tea or coffee could survive the heat treatment, thus exhibiting antiradical activity in cake samples fortified with STP or SCP. Previous reports showed similarities with our findings, where various bakery goods fortified with raw tea or coffee powders, their extracts, or their spent forms presented higher antioxidant activities compared to the controls. ,, …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies attributed the antioxidant capacities of coffee and tea to their phenolic contents. ,, Our findings indicate that the residual phenolic compounds in spent tea or coffee could survive the heat treatment, thus exhibiting antiradical activity in cake samples fortified with STP or SCP. Previous reports showed similarities with our findings, where various bakery goods fortified with raw tea or coffee powders, their extracts, or their spent forms presented higher antioxidant activities compared to the controls. ,, …”
Section: Resultssupporting
confidence: 91%
“…Spent coffee powder had a total phenolic content that was 23.5 times higher than wheat flour . In addition, the spent coffee powder had the highest total phenolic content.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…A study by Antonios et al, (2017) investigating the effect of substituting rye flour in cookies at ratios of 10%, 20%, 30%, and 40% showed that higher rye flour substitution led to an increasing trend in TPC, peaking at 53 mgGAE/100 g DM at a 40% substitution ratio [39]. Similarly, Tran et al, (2021) indicated that gradually adding 5-25% coffee grounds to cookie products resulted in a progressive increase in TPC from 204 mgGAE/100 g DM to 678 mgGAE/100 g DM [40]. In contrast, Chinedum et al, (2014) recorded that as the replacement ratio of tapioca flour increased from 10% to 40%, the TPC in bread decreased from 16.35 mgGAE/100 g DM to 3.37 mgGAE/100 g DM [41].…”
Section: Physicochemical Propertiesmentioning
confidence: 96%
“…The changes in DPPH radical scavenging activity due to the addition of JSF and JSS were related to the TPC in cookies [42]. A study by Tran et al, (2021) reported that DPPH radical scavenging activity increased gradually from 140 mgAAE/100 g DM to 3813 mgAAE/100 g DM when the addition rate of 5-25% coffee grounds to cookie products was increased [40]. These findings were similar to the results obtained by Antonios et al, (2017), where the DPPH radical scavenging activity increased from 17.55 mgAAE/100 g DM to 24.68 mgAAE/100 g DM with an increase in the rye replacement ratio from 10% to 40% [39].…”
Section: Physicochemical Propertiesmentioning
confidence: 98%